Analysis of Student User Satisfaction with the Learning Management System (LMS) at Gajayana University - Donda Anjelina Elu; HM HM Amir; Fachrudin Pakaja (oneamrd (One a Mllions Dreams Corporation), 2025)
The development of information technology has driven the transformation of learning through e-learning systems, one of which is the use of a Learning Management System (LMS). Gajayana University Malang has implemented a web-based LMS to support the online teaching and learning process. This study aims to analyze the level of user satisfaction—in this case students—with the use of the LMS using the DeLone and McLean Model approach. This model measures the success of an information system through six variables: system quality, information quality, service quality, impact of use, user satisfaction, and net benefits. This study used a quantitative approach by distributing questionnaires to 95 active students of Gajayana University Malang who have used the LMS. Data were analyzed using multiple linear regression through SPSS. The results showed that system quality, service quality, and impact of use significantly influenced user satisfaction, while information quality did not have a significant influence. Furthermore, user satisfaction was proven to have a positive effect on perceived net benefits